Bridging the planet radius valley: stellar clustering as a key driver for turning sub-neptunes into super-earths - Kruijssen, Diederik; Longmore, Steven N.; Chevance, Mélanie (The astrophysical journal. Part 2, Letters, 2020)
Extrasolar planets with sizes between that of the Earth and Neptune (Rp = 1-4 R⊕) have a bimodal radius distribution. This “planet radius valley” separates compact, rocky super-Earths (Rp = 1.0-1.8 R⊕) from larger sub-Neptunes (Rp = 1.8-3.5 R⊕) hosting a gaseous hydrogen-helium envelope around their rocky core. Various hypotheses for this radius valley have been put forward, which all rely on physics internal to the planetary system: photoevaporation by the host star, long-term mass loss driven by the cooling planetary core, or the transition between two fundamentally different planet formation modes as gas is lost from the protoplanetary disk. Here we report the discovery that the planet radius distribution exhibits a strong dependence on ambient stellar clustering, characterized by measuring the position-velocity phase space density with Gaia. When dividing the planet sample into “field” and “overdensity” subsamples, we find that planetary systems in the field exhibit a statistically significant (p = 5.5 × 10−3) dearth of planets below the radius valley compared to systems in phase space overdensities. This implies that the large-scale stellar environment of a planetary system is a key factor setting the planet radius distribution. We discuss how models for the radius valley might be revised following our findings and conclude that a multiscale, multiphysics scenario is needed, connecting planet formation and evolution, star and stellar cluster formation, and galaxy evolution.
Gesehen am 17.02.2022